If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x+2)(x-9)=(7x+17)
We move all terms to the left:
(x+2)(x-9)-((7x+17))=0
We multiply parentheses ..
(+x^2-9x+2x-18)-((7x+17))=0
We calculate terms in parentheses: -((7x+17)), so:We get rid of parentheses
(7x+17)
We get rid of parentheses
7x+17
Back to the equation:
-(7x+17)
x^2-9x+2x-7x-18-17=0
We add all the numbers together, and all the variables
x^2-14x-35=0
a = 1; b = -14; c = -35;
Δ = b2-4ac
Δ = -142-4·1·(-35)
Δ = 336
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{336}=\sqrt{16*21}=\sqrt{16}*\sqrt{21}=4\sqrt{21}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-14)-4\sqrt{21}}{2*1}=\frac{14-4\sqrt{21}}{2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-14)+4\sqrt{21}}{2*1}=\frac{14+4\sqrt{21}}{2} $
| 8x+21=3/11 | | 5(y-1)+16(2y+3)=3(2y-7) | | 10*62=n*6.2 | | y=-9-4-9 | | 0*53=n*34 | | 3(4x+1)=6x+2 | | n/5.9=11 | | 2x+8-x=3x-12 | | 9.8x=63.7 | | -5x=10-15. | | 28*n=7*12 | | 5x=10-15. | | (-6d=2)-(7=2d) | | 36*n=36 | | p/1.2=25/15 | | 17/15+s/15=-4 | | 18+30=6(2x-1) | | 13+4K=13+5k | | -67b+6=9b+43 | | 1=8x-6=2=7x | | 8p-8=6(-7p+7) | | 5x-81=360 | | 63-x=2x=3 | | (7x^2-27)=(6x^2-6x) | | 4(m-4)-6=-31-5m | | 9^2-18=8^2-7x | | 18-2|c+7|=12 | | -42v+33=8v | | (9x-18)=(8x-7x) | | 1/m+2-4=4/m+2 | | 4x+92=0+80x | | -4x+3(x-8)=7(2x-4)-11 |